2022
DOI: 10.3233/jpd-223190
|View full text |Cite
|
Sign up to set email alerts
|

Including People with Parkinson’s Disease in Clinical Study Design and Execution: A Call to Action

Abstract: The proactive inclusion of patients in the design and execution of clinical studies has been an emerging focus for decades. Such participatory research helps to a design studies better, by addressing relevant research questions and defining outcomes that matter to patients. Yet, much remains to be learned about the best methods and exact impacts of patient engagement in research in general, and more specifically, about the specific challenges that come with Parkinson’s disease. Here we present the lived experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“… 6 We therefore echo the calls for a broader and more accurate view of Parkinson’s through the use of diverse imaging and inclusive research participation. 27 , 28 , 29 , 30 While acknowledging that no single image can adequately reflect the diversity in background, phenotypes, and experiences in PD, it is important that images, both in public and in medical teachings, are consistent with the advances in Parkinson’s research and encourage discussion about how Parkinson’s is represented.…”
Section: Discussionmentioning
confidence: 99%
“… 6 We therefore echo the calls for a broader and more accurate view of Parkinson’s through the use of diverse imaging and inclusive research participation. 27 , 28 , 29 , 30 While acknowledging that no single image can adequately reflect the diversity in background, phenotypes, and experiences in PD, it is important that images, both in public and in medical teachings, are consistent with the advances in Parkinson’s research and encourage discussion about how Parkinson’s is represented.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of patients in the definition of research-agendas and study designs can improve studies’ feasibility, cost-effectiveness, and validity ( Schipper et al, 2014 ; Roudini et al, 2023 ). Sporadically, investigators pioneered patient engagement in PD studies and reported about this endeavor ( Meinders et al, 2022 ; Evers et al, 2023 ). Meinders and colleagues recently published general advice and experiences with patient engagement in PD studies, but specific reports on patient engagement for naturalistic monitoring studies with DBS patients lack, to our best knowledge.…”
Section: Current Literaturementioning
confidence: 99%
“…Stacey describes how Matthew advised her 'on things like providing larger buttons to press which are easier to use with their movement symptoms, as well as breaking up longer, difficult tests with shorter, easier ones and making text bigger and more readable' (see also Meinders et al, 2022). This fits with the wider literature on the importance of people with lived experience advising on the comfort of participants (Gowen et al, 2019), trialling research tools and having a role in training researchers (Lea et al, 2020).…”
Section: Background and Initial Contactmentioning
confidence: 99%